Ambrosiaster’s Revisions of His Commentary on Romans and Roman Synodal Statements about the Holy Spirit - de Bruyn, Theodore (Université d'Ottawa | University of Ottawa, 2010)
Ambrosiaster’s Commentary on Romans exists is three apparently sequential versions (alpha, beta, and gamma). In alpha and beta Ambrosiaster modifi ed the comments on Romans 1:3 and 8:26-27 to emphasize that the Holy Spirit is divine (against the Pneumatomachians) and that Christ is fully human (against Apollinaris). These changes are examined in light of contemporary Roman synodal letters from the 370s and early 380s. The comments on Romans in alpha appear to belong to a period before 375 and possibly before 371, the changes introduced in beta correspond to theological developments in Rome in the second half of the 370s, and the changes introduced in gamma appear to belong to the early 380s. However, there are still difficulties in the dating of the versions that remain to be resolved.
Keywords: Ambrosiaster; Commentary on Romans; Tome of Damasus; Holy Spirit; Trinitarian theology